ANIMASI INTERAKTIF PENGETAHUAN DASAR BAHASA DAN MATEMATIKA BERBASIS MULTIMEDIA - Sidik Sidik; Nanda Annisa (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2017)
Currently, there are many kindergartens that way of delivering lessons with the method of lectures / conventional. Sometimes explaining learning materials to children aged 5-6 (five-six) years or below kindergarten students is not easy. Such as Tadika Puri kindergarten which was established in 1977 and to this day still use the method of a mirror. The process of understanding students who are slow in capturing learning materials in because lessons taught less interesting. Therefore required new media and support methods for the learning process becomes more effective teaching with interactive multimedia-based learning applications. The research method used in this writing is a qualitative method with a descriptive approach that is equipped with research using questionnaires and interviews with the respondents who have been predetermined. The result of the interactive animation design of basic knowledge of language and mathematics can help students in understanding the vocabulary of language and mathematics easily because it is conveyed with an interesting accompanied by interactive pictures and sounds.